2007
DOI: 10.1364/oe.15.014057
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric motility-contrast imaging of tissue response to cytoskeletal anti-cancer drugs

Abstract: Microscopic imaging of cellular motility has recently advanced from two dimensions to three dimensions for applications in drug development. However, significant degradation in resolution occurs with increasing imaging depth, limiting access to motility information from deep inside the sample. Here, digital holographic optical coherence imaging is adapted to allow visualization of motility in tissue at depths inaccessible to conventional motility assay approaches. This method tracks the effect of cytoskeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 25 publications
(23 reference statements)
1
87
0
Order By: Relevance
“…Taking it one step further, DHM can be used for tomographic measurements (Massatsch et al, 2005) that enable analysis of sub-cellular motion from deep within living tissues (Jeong et al, 2007a), along with valuable 3-D-reconstruction of the object (volumetric visualization) (Jeong et al, 2007b). Sun and colleagues showed that they could follow the movement of blood cells in vivo in a tadpole blood vessel (Sun et al, 2008).…”
Section: Tissue Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking it one step further, DHM can be used for tomographic measurements (Massatsch et al, 2005) that enable analysis of sub-cellular motion from deep within living tissues (Jeong et al, 2007a), along with valuable 3-D-reconstruction of the object (volumetric visualization) (Jeong et al, 2007b). Sun and colleagues showed that they could follow the movement of blood cells in vivo in a tadpole blood vessel (Sun et al, 2008).…”
Section: Tissue Studiesmentioning
confidence: 99%
“…cell morphology or motility and migration. DHM has also been used for studies on spheroids (Yu et al, 2003;Jeong et al, 2007b). Spheroids are clusters of cells that serve as in vitro tumor models which can be used for e.g.…”
Section: Tissue Studiesmentioning
confidence: 99%
“…Motility contrast imaging (MCI) [13] is an extension of digital holographic optical coherence imaging utilizing such dynamic speckle. MCI uses fully developed speckle fields that carry little structural information.…”
Section: Introductionmentioning
confidence: 99%
“…One of the many possible applications of MCI is to image the effects of the largest class of anticancer drugs [13], i.e. the antimitotic drugs that arrest the cellular motion associated with mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used to investigate various cellular dynamics such as drug-induced changes in cells [27][28][29]. In [30], digital holographic microscopy (DHM) is used to monitor laser microsurgery on cells, for quantitative evaluation of the damage and repair of cells and cellular organelles in real time.…”
Section: Introductionmentioning
confidence: 99%